Tokoh Surrya (Juru Pāndai) dalam Penulisan Prasasti Gunung Tua (Bhatāra Lokanātha) - Churmatin Nasoichah (Berkala Arkeologi Sangkhakala, 2009)
AbstractThe mention of the name of Pāndai is rarely to be found in an inscription without any mention of the name of a king, royal official or a person who receives the inscription. His ability in mastering bilingual and expertise in making a statue Lokanātha, which is an important figure in Buddhism, not make an ordinary pāndai. He is mentioned in the inscription by the name of Suryya. In Mandailing society, Suryya is associated with their ancestors named Namora Pande Bosi.